Sample-level PRRSV RT-PCR prevalence in pigs in mainland China (2004–2025): A systematic review and meta-analysis - Mengke Si; Yiwei Wang; Xiang Li; Junxue Qiu; Xiaoyu Chong; Baolei Yang; Mingfeng Chu; Yuchen Liang; Wei Cheng; Jingyan Zhang; Xuelong Chen; Yanping Qi (Preventive Veterinary Medicine, 2026)

Benzimidazole functionalization enables efficient multi-resonance TADF with accelerated spin-flipping and balanced charge transport - Ji-Hua Tan; Si-Wei Chen; Xin-Lu Li; Han-Nan Shi; Xiao-Long Liu; Yao-Zu Su; Xiaofeng Wang; Jun-Hua Zhuang; Chengxiang Shi; Jia-Ming Jin; Shaoyun Yin; Jia-Xiong Chen; et al. (Chemical Engineering Journal, 2026)

Dual-responsive and CD44-targeted nanotherapy to remodel the fibrotic niche for reversing liver fibrosis - Jingwei Li; Jiahao Chen; Lingling Wang; Wei Zhao; Yan Xia; Jinhang Zhang; Jie Zhou; Haiying Song; Xinghe Ji; Zijing Zhang; Shuting Qiu; Xiandan Jing; et al. (Chemical Engineering Journal, 2026)

An integrated experimental and computational study on a COX-2-targeted AIE probe for precise cancer cell imaging via restriction of intramolecular rotation - Jianxi Liu; Shengfa Song; Yonglin Zhang; Jiale Hu; Shulin Chen; Lulu Zhu; Li Shen; Zhen Sun; Ying Xue; Hao Jiang; Wei Ji; Jinmei Sun; et al. (Analytica Chimica Acta, 2026)

Measuring and enhancing urban water supply resilience: A dynamic coupling framework and its application in Beijing - Yanping Liu; Jiahua Wei; Minglei Hou; Jiaqi Xu; Chenfei Yan; Li Xue (Sustainable Cities and Society, 2026)

Corrigendum to “Spatiotemporal prediction of PM2.5 concentration over the Beijing–Tianjin–Hebei region based on forecasting, interpolation, and correction of ERA5 precipitable water vapor” [J. Atmos. Sol. Terr. Phys. 285 (2026), Article 106859] - Xiangshun Meng; Yanping Liu; Yong Wang; Chunhong Liu; Wei Du; Yingliang Wang (Journal of Atmospheric and Solar-Terrestrial Physics, 2026)

Pre-lithiation strategy enhancing interfacial stability of carbon-coated SiO anodes via controlled formation of LixSiyOz for high-energy lithium-ion batteries - Hong Dong; Yanping Ma; Xiaobin Zhou; Jinying Hou; Juan Xin; Mingzhu Wei; Jianyao Zhu; Shiyou Li; Ya-Jun Cheng (Chemical Engineering Journal, 2026)

Dysregulation of CD36 and CPT1A is associated with fatty acid metabolic disorder and cardiomyocyte injury after high-cervical spinal cord injury - Yanping Zhang; Shihong Huang; Lifei Chen; Liqin Wei; Qinfeng Huang; Linshen Huang; Hui Chen (Molecular and Cellular Biochemistry, 2026)

Erastin-sensitive VDAC2 contributes to time-course peritoneal fibrosis via ferroptosis signaling induction - Wenfeng Wei; Yanping Qiu; Rong Luo; Yangping Feng (Molecular and Cellular Biochemistry, 2026)

Parametric investigation of roll damping for a polar icebreaker using CFD and free-decay experiments - Wei Zhang; Yadong Liu; Yanping He; Chengming Hao; Hanyi Yao; Houfei Wu (Ocean Engineering, 2026)

Electric field-assisted simultaneous microextraction of ultrashort- to long-chain perfluorocarboxylic acids prior to HPLC-MS/MS quantification - Fenghong Wei; Pei Wang; Junjun Hu; Yanping Zheng; Xiaojia Huang (Journal of Hazardous Materials, 2026)

Spatiotemporal prediction of PM2.5 concentration over the Beijing–Tianjin–Hebei region based on forecasting, interpolation, and correction of ERA5 precipitable water vapor - Xiangshun Meng; Yanping Liu; Yong Wang; Chunhong Liu; Wei Du; Yingliang Wang (Journal of Atmospheric and Solar-Terrestrial Physics, 2026)

Sleep Duration and Epilepsy Risk: Mendelian Randomization and Functional Validation of CACNA1A rs2228130-Related Inhibitory Synaptic Dysfunction - Xun Li; Yuying Hou; Yanping Ren; Wei Yue (NeuroMolecular Medicine, 2026)

Integrated Application of Iso-Seq and RNA-Seq Analyses to Uncover Genes Involved in Ovarian Development in Platypharodon extremus - Zhuoyu Yang; Yanping Zhang; Wei Ka; Wenjing He; Yujie Yang; Wenlong Jiao; Jianlin Wang (Fishes, 2026)
This study focused on Platypharodon extremus, a species endemic to the Qinghai–Tibet Plateau, and systematically analyzed its reproductive biology, sex steroid hormones, ovarian histology, and transcriptomic characteristics throughout its complete reproductive cycle (August 2020 to June 2021). The results demonstrated that the body length, height, body weight, and gonadal weight of female individuals continuously increased with age, while the Gonadosomatic index (GSI) was lowest during the breeding season (June–August) and gradually rose during the non-breeding period. Serum estradiol (E2) and progesterone (P4) exhibited rhythmic fluctuations corresponding to ovarian development: E2 rose from 25.77 ng/L in stage-I to 146.00 ng/L in stage-V, then declined post-ovulation; P4 increased from 59.88 pmol/L in stage-I to 239.03 pmol/L in stage-V, showing a significant decrease after ovulation. Histological observations classified ovarian development into stages I–VI, clearly delineating the complete process from oogonium proliferation, cortical vesicle formation, yolk accumulation, maturation to postpartum regression. To explore molecular changes during the transition from vitellogenesis to oocyte maturation, we built a reference transcriptome with 30,060 non-redundant transcripts (average length = 1975 bp) using PacBio and Illumina data, and 91.87% of these transcripts received functional annotation hits against public databases. A comparative differential expression analysis was performed between ovarian stage III (active yolk accumulation) and stage V (oocyte fully matured). A total of 11,324 differentially expressed genes were identified (5249 upregulated and 6175 downregulated) between these two stages. GO enrichment analysis revealed predominant involvement in cellular processes, cellular components, and catalytic activities, while KEGG analysis demonstrated significant enrichment in metabolic pathways, PI3K-Akt, MAPK, and calcium signaling pathways. Quantitative PCR (qPCR) validation confirmed that candidate genes, including pik3a, calm, mapk1 map2k ddx49, and igf2 were significantly upregulated at stage V. These differentially expressed genes (DEGs) may represent potential molecular signatures linked to the transition from vitellogenesis to oocyte maturation. Our integrated transcriptomic and qPCR data identify potential gene candidates involved in ovarian maturation; however, these findings reveal correlation rather than direct regulatory causality. This study offers fundamental data and theoretical insights for understanding the reproductive regulatory mechanisms and aquaculture management of this endemic species.

Phage therapy: A novel strategy to combat drug-resistant Salmonella Pullorum infection in chickens - Hongzhe Zhao; Shilong You; Jiahao Fu; Xiaoyu Xiong; Yingying Ma; Xiaona Wang; Rongyan Li; Fei Teng; Mingze Chen; Wei Wu; Guiwei Li; Yanping Jiang; et al. (Veterinary Microbiology, 2026)

A Study on the Species Diversity, Mating Types, and Clinical Relevance of Trichophyton mentagrophytes/interdigitale Complex Infections in Guizhou Province - Wei Hu; Kexin Xu; Jing Zhou; Wanglan Luo; Songgan Jia; Xiangyu Liu; Zhengling Shang; Yinhui Jiang; Zhi Liu; Yanping Jiang (Mycopathologia, 2026)

Molecular dynamics simulation of polyamide based reverse osmosis for boron removal - Yawei Du; Mengru Cui; Jingxin Wei; Yanping Li; Yize Liu; Shizhao Wang; Zhiyong Ji (Desalination, 2026)

Strain-specific impacts of Pichia kudriavzevii on metabolite profiles and microbial community dynamics in Chinese Baijiu fermentation: Integrated metabolomics and metagenomics analysis - Boqin Zhang; Mengbo Wang; Jia Zheng; Chenxi Yu; Chunhui Wei; Junyu Ren; Shouying Sun; Guoming Wang; Jinhua Wang; Yanping Lu; Liangcai Lin; Cuiying Zhang (International Journal of Food Microbiology, 2026)

Intraspecific Variations and Characteristics of Clinical, Physiological, and Antifungal Susceptibility Profiles of Trichophyton rubrum in Southwest China - Yanni Deng; Wanglan Luo; Hao Hu; Jing Zhou; Qian Zhang; Songgan Jia; Wei Lei; Zhengling Shang; Yinhui Jiang; Zhu Zeng; Yanping Jiang (Mycopathologia, 2026)

Inhibition of potato common scab by Bacillus subtilis XT11 and its reshaping of the microbial community in potato geocaulosphere soil - Ning Liu; Minghao Lv; Yongdong Wang; Huimin Ma; Wei Fan; Junjie Ma; Jiguang Wang; Yanping Gao; Jinbiao Ma; Bo Zhou; Wenchong Shi; Zheng Gao (World Journal of Microbiology and Biotechnology, 2026)

Identification and validating native biocontrol bacteria Bacillus strain MZ3-12 against bacterial wilt - Xiao Zhou; Yue Qing; Yanping Wang; Haibin Deng; Jun Wang; Mi Kuang; Xuefeng Luo; Chenran Zhao; Zheng Sun; Ye Wang; Liang Yang; Wei Ding (Pesticide Biochemistry and Physiology, 2026)

The insecticidal activity and mechanism of the Cinnamomi ramulus (Lauraceae) essential oil against Tribolium confusum Jaquelin Du Val, 1868 (Coleoptera: Tenebrionidae): insights from transcriptomic and metabolomic profiles - Qianqian Lian; Jianji Zhao; Yiqing Li; Hui Tang; Yanping He; Qiuling Tang; Wei Zhang; Jie Bi (Journal of Stored Products Research, 2026)

Quasi-real-time retrieval of ERA5 precipitable water vapor over mainland China - Xiangshun Meng; Yong Wang; Yunlong Zhang; Wei Du; Yanping Liu; Xiao Liu (Advances in Space Research, 2026)

Long-distance lateral migration, accumulation and dissipation of natural gas in the northeastern Ordos Basin, China - Yang Qin; Chiyang Liu; Junfeng Zhao; Faqi He; Wei Zhang; Yanping Ma; Lihua Yang; Deyong Shao; Nan Du; Fuyu Chen (Gondwana Research, 2026)

Molecular Epidemiology, Mating Types, Clinical, and Physiological traits of Microsporum canis in Humans and Companion Animals (Cats and Dogs) in the Guiyang Region, Southwest China - Hao Hu; Bin Jiao; Yanni Deng; Wanglan Luo; Jing Zhou; Wei Lei; Zhengling Shang; Yinhui Jiang; Zhengrong Wang; Zhu Zeng; Yanping Jiang (Mycopathologia, 2026)

Evaluation of salt tolerance in Agropyron Gaertn.: key indicators, optimal conditions, and implications for crop improvement - Jiarui Zou; Jing Yang; Ying Liu; Yanping Yang; Lai Wei; Haiming Han; Shenghui Zhou; Weihua Liu; Jinpeng Zhang; Lihui Li; Yonghe Che (Genetic Resources and Crop Evolution, 2026)

Advances in acetylcholinesterase-based biosensing technologies for organophosphorus pesticide detection: A comprehensive review (2020–2024) - Qian Zhang; Jing Yu; Yanping Wei; Rong Yang; Jin Liu; Yangyang Su; Die Gao; Jing Zeng (Food Chemistry, 2025)

Overexpression of CYP6CY36 and CYP380C34 contributes to metabolic resistance of Myzus persicae (Sulzer) to flupyradifurone - Qiuling Tang; Jinfeng Hu; Chengfeng Zheng; Wei Zhang; Jie Bi; Yanping He (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Population pharmacokinetic characteristics of tacrolimus in Chinese lung transplant recipients and optimisation of dosing regimen during the early post-transplantation phase - Shouning Zhou; Qiaoyan Lian; Huilong Luo; Hui Xie; Yanping Guan; Jianxing He; Li Wei; Chunrong Ju (European Journal of Clinical Pharmacology, 2025)

Complete genome sequence and molecular characterization of a novel potyvirus (sweet potato virus H) infecting sweet potato - Wei Tang; Jukui Ma; Yanping Tian; Xiao Yin; Jingwei Chen; Dongjing Yang; Fangyuan Gao; Zhao Liang; Cong Tong; Chengling Zhang; Houjun Sun (Archives of Virology, 2025)

New interpretation of the Rb/Sr ratio of the Ili loess, northeastern Central Asia - Yanping Wang; Yougui Song; Yue Li; Hamid Gholami; Haoru Wei; Mengxiu Zeng; Xiuling Chen; Li Han (Quaternary Science Reviews, 2025)

Adapting to hypo-salinity: Molecular mechanisms in giant clams and symbionts with implications for coral reef resilience under climate change - Zhen Zhao; Xixi Duan; Tao Zhang; Siqi Bi; Zohaib Noor; Shuming Guo; Zonglu Wei; Yinjie Zhang; Yanping Qin; Haitao Ma; Ying Pan; Ziniu Yu; et al. (Environmental Research, 2025)

Editorial Expression of Concern: The nuclear translocation of endostatin is mediated by its receptor nucleolin in endothelial cells - Nan Song; Yanping Ding; Wei Zhuo; Ting He; Zhiguang Fu; Yang Chen; Xiaomin Song; Yan Fu; Yongzhang Luo (Angiogenesis, 2025)

Metabolic engineering of a high-light tolerant cyanobacterium Synechocystis sp. PCC 6803 for efficient biosynthesis of β-farnesene from CO2 - Wei Zhang; Jie Zhou; Yanping Zhang; Yin Li (Systems Microbiology and Biomanufacturing, 2025)

Evolution and prediction of drought-flood abrupt alternation in mainland China using an improved index - Yiming Tong; Yu Chen; Yanping Qu; Virgílio A. Bento; Hongquan Song; Han Qiu; Wei Shui; Jingyu Zeng; Qianfeng Wang (Climate Dynamics, 2025)

Exploring the symbiotic resilience of boring giant clams and zooxanthellae during heatwave conditions: An investigation into strategic countermeasures - Zhen Zhao; Siqi Bi; Liqiang Zhao; Zohaib Noor; Shuming Guo; Zonglu Wei; Xixi Duan; Yanping Qin; Haitao Ma; Ying Pan; Ziniu Yu; Kotaro Shirai; et al. (Aquaculture, 2025)

Nosema or Vairimorpha: Genomic/proteomic support to a complex socio-economic issue rooted in taxonomic change - Jamie Bojko; James Becnel; Edouard Bessette; Sam Edwards; Jing Gao; Wei-Fone Huang; Nataša Katanić; Amjad Khalaf; Tian Li; Jonathan W. Snow; Leellen F. Solter; Cheyenne E. Stratton; et al. (Journal of Invertebrate Pathology, 2025)

Comparative analysis of sheep, goat, and cow milk based on non-targeted metabolomics - Jiaxin Liu; Zhongshi Zhu; Yanping Huang; Jianping Qin; Li Wang; Mengyao Wei; Xiaorui Liu; Liang Xu; Hao Yuan; Xiaopeng An; Lei Zhang; Yuxuan Song (International Dairy Journal, 2025)

Expert consensus on cryosurgery therapy of mucosal melanoma on head and neck - Yadong Wu; Guoxin Ren; Moyi Sun; Zhangui Tang; Longjiang Li; Jian Meng; Zhijun Sun; Shaoyan Liu; Yue He; Wei Shang; Bo Li; Jie Zhang; et al. (Cryobiology, 2025)

Mn-doped copper slag with oxygen vacancies boosts peroxymonosulfate activation for ofloxacin rapid removal - Linjin Li; Yaoze Wang; Guangfei Qu; Nanqi Ren; Yanping Liu; Jiao Wei; Dehui Kong; Changyi He; Minhua Cheng; Yingying Cai; Xiaofei Li; Rui Xu (Journal of Water Process Engineering, 2025)

Variations in Central Asian dust activity and potential driving mechanisms over the past 80 kyr - Haoru Wei; Yougui Song; Yanping Wang; Mingyu Zhang; Hamid Gholami; Shugang Kang; Yue Li; Shukhrat Shukurov; Nosir Shukurov; Rustam Orozbaev (Gondwana Research, 2025)

Enhancing manganese redox-driven nitrogen removal by integrating manganese ore with microelectrolysis into constructed wetlands - Xiaoxiao Hou; Wei Huang; Xinshan Song; Yingying Liu; Yanping Xiao; Xiaoxiang Zhao; Dong An (Bioresource Technology, 2025)

Influence of tin doping on the activity and mechanism of CeO2 catalyst for selective catalytic reduction of NO with NH3 - Jingsong Zhou; Yanping Du; Yuqing Qiao; Fei Zhou; Zhou Liu; Zhibo Xiong; Mengqi Liu; Wei Lu (Journal of Environmental Chemical Engineering, 2025)

W2O6/CoFe2O4: An efficient catalyst to activate peroxymonosulfate for the elimination of antibiotic-resistant bacteria and genes in aquaculture effluent - Yanqiong Zhang; Muting Yan; Gaoling Wei; Fengru Lu; Feng Li; Peng Liu; Yanping Zhu; Han Gong (Journal of Environmental Chemical Engineering, 2025)

Research on PWV fusion based on ERA5 PWV and FY-4A PWV in Chinese mainland - Wei Du; Yong Wang; Xiao Liu; Jing Huang; Yanping Liu; Xiangshun Meng (Journal of Atmospheric and Solar-Terrestrial Physics, 2025)

Synergizing lattice matching and transient N–Li bonds to boost sulfur redox kinetics and regulate uniform lithium deposition in practical Li–S batteries - Yantao Wang; Huiqin Chen; Wenjuan Wu; Jinlong Li; Guangxin Zhang; Chunyan Wei; Shiyu Wang; Linlin Zhang; Yanping Zheng; Huanhuan Li (Chemical Engineering Journal, 2025)

Comparison of genetic diversity and population structure of Saccostrea mordax lineages A, B, and C across South China Sea and Celebes Sea - Yinjie Zhang; Haitao Ma; Chenghui Han; Zhen Zhao; Zonglu Wei; Xixi Duan; Jiangwei Li; Yanping Qin; Jun Li; Ziniu Yu; Ying Pan; Yuehuan Zhang (Frontiers in Marine Science, 2025)
Saccostrea mordax is an ecologically important bivalve species and a potential genetic resource for oyster breeding that inhabit in the Indo-Western Pacific region, characterized by three distinct lineages: A, B, and C. However, limited information is available about its genetic variation and genetic structure. The present study was conducted to study genetic diversity and population structure of S. mordax lineages A, B, and C based on mitochondrial COI gene data across the South China Sea and Celebes Sea. The UPGMA phylogenetic tree among populations, BI phylogenetic tree among individuals and median network revealed three main clusters, corresponding to S. mordax lineages A, B, and C. The results of K2P sequence divergence, pairwise Φ st, gene flow and AMOVA indicated clear genetic differences among the lineages, combined with sympatric in all 7 geographical populations, these suggests lineages A and B are transitional periods of new species formation. Moreover, different patterns of population subdivision were found within lineages A, B and C. In lineage A, significant genetic differentiation was only observed between YM (Celebes Sea) and other populations (South China Sea), with a significant correlation between geographical distance and genetic distance among populations. In lineages B and C, there was no genetic differentiation between YM (Celebes Sea) and other populations (South China Sea), and no significant correlation between genetic distance and geographical distance among populations. The population history analyses indicated that populations of lineage A have experienced a recent sudden expansion, while populations of lineages B and C were large stable. These findings are essential for the conservation, sustainable utilization, and ecological restoration of S. mordax .

Hybrid Path Planning Method for USV Based on Improved A-Star and DWA - Yan Liu; Zeqiang Sun; Junhe Wan; Hui Li; Delong Yang; Yanping Li; Wei Fu; Zhen Yu; Jichang Sun (Journal of Marine Science and Engineering, 2025)
This paper presents a hybrid path planning method that integrates an enhanced A-Star algorithm with the Dynamic Window Approach (DWA). The proposed approach addresses the limitations of conventional A-Star algorithms in global path planning, particularly their inability to adaptively avoid obstacles in real-time. To improve navigation safety, the A-Star search strategy is enhanced by avoiding paths that intersect with obstacle vertices or pass through narrow channels. Additionally, a node optimization technique is introduced to remove redundant nodes by checking for collinearity in consecutive nodes. This optimization reduces the path length and ensures that the path maintains a safe distance from obstacles using parallel lines. An advanced Bézier curve smoothing method is also proposed, which adaptively selects control points to improve path smoothness and driving stability. By incorporating these improvements, the enhanced A-Star algorithm is combined with DWA to facilitate dynamic obstacle avoidance while generating global paths. The method accounts for the kinematic characteristics of the USV, as well as physical constraints such as linear and angular velocities, enabling effective handling of obstacles in dynamic environments and ensuring safe navigation. Simulation results demonstrate that the proposed algorithm generates secure global paths, significantly optimizing node count, path length, and smoothness, while effectively avoiding dynamic obstacles, thus ensuring safe navigation of the USV.

Critical review on food packaging strategy against spoilage - Lei Liu; Youwei Jiang; Kun Wan; Yanping Wei; Du Tuo; Chuanqin Zhou; Quanguo He; Yimin Tan (Food and Humanity, 2025)

Biosynthetic small molecule antigens mimics medicated lateral flow immunoassay for mycotoxin Fumonisin B1 using nanobody fusion proteins - Chong Cai; Yuheng Xia; Yuanzhen Guo; Binhui Huang; Tailong Wei; Yun Liang; Qiannan Gao; Zhui Tu; Yanping Li; Qinghua He (Journal of Hazardous Materials, 2025)

Research on the fusion of PWV over the Beijing-Tianjin-Hebei region based on ERA5 PWV and FY-4A PWV - Wei Du; Yong Wang; Xiangshun Meng; Yanping Liu; Xiao Liu (Advances in Space Research, 2025)

Enhancing humification in high-temperature composting: Insights from endogenous and exogenous heating strategies - Chaoyue Zhao; Feng Ma; Youzhao Wang; Xu Li; Yanping Zhang; Zhipeng Wang; Wei Xiong; Xiaolong Gao; Yongguang Ma; Fuxin Yang; Tong Zhu (Bioresource Technology, 2025)

New insights into interfacial dynamics and mechanisms of biochar–derived dissolved organic matter on arsenic redistribution in Schwertmannite - Xiaofei Li; Tianfu Li; Yanfu Wei; Xiaohu Jin; Suresh C. Pillai; Jun Zhang; Dian Chen; Xiaolian Wu; Yanping Bao; Xueding Jiang; Hailong Wang (Environmental Pollution, 2025)

An enhancer–promoter-transcription factor module orchestrates plant immune homeostasis by constraining camalexin biosynthesis - Ying Zhang; Meng Tang; Yi Zhang; Qinglin Cheng; Lijiang Liu; Wei Chen; Jiatao Xie; Jiasen Cheng; Yanping Fu; Bo Li; Daohong Jiang; Xiao Yu (Molecular Plant, 2025)

Phosphorus-oxygen modified anthracene-based emitters for high-efficiency deep-blue OLEDs approaching the BT.2020 blue standard - Ruicheng Wang; Yihong Zhu; Dehua Hu; Jie Hu; Si-wei Chen; Jieying Lin; Longjiang Xing; Yanping Huo; Shaomin Ji (Chemical Engineering Journal, 2025)

Highly degradable bio-based plastic with water-assisted shaping process and exceptional mechanical properties - Jingjing Wang; Yuan Liang; Yuhan Chen; Hai Wan; Wenbin Jin; Ting Luo; Yuwei Chen; Peng Wei; Shuohan Huang; Yong He; Yanping Wang; Yumin Xia (Carbohydrate Polymers, 2025)

Dynamic aromatics: Evaluating fragrance quality shifts and implementation of real-time rapid detection in Hedychium cut flowers during senescence - Yiwei Zhou; Qin Wang; Xue Wei; Ting Gao; Farhat Abbas; Fulong Yan; Jingjuan He; Yunyi Yu; Rangcai Yu; Yanping Fan (Postharvest Biology and Technology, 2024)

Research on parametric roll of the polar environmental transport ship based on time-domain Rankine panel method - Wei Zhang; Yadong Liu; Yanping He; Yan Zhou; Dong Wang; Yuying Tang; Jianmei Chen (Ocean Engineering, 2024)

Promotional effect of microwave radiation treatment on the desorption of CO2 from mono-ethanolamine (MEA) solution over FeOOH catalyst - Haoran Zhang; Junge Lv; Zhibo Xiong; Huancong Shi; Jing Jin; Mengqi Liu; Yanping Du; Wei Lu (Journal of Environmental Chemical Engineering, 2024)

Field experiment on transient thermal comfort in a Chinese railway station – High temperature exposures - Xiaowen Su; Wei Liu; Richard de Dear; Liangliang Sun; Yanping Yuan (Building and Environment, 2024)

Multi-drug loaded electrospinning nanofibers promote healing with less scar formation by remodeling wound microenvironment via modulating TGF-β1/Smads/EN1 signal - Xiaoyan Zeng; Zhenfeng Guan; Reyisha Yusufu; Siyi Li; Qi WU; Yanping Feng; Tiantian Chen; Muxiang Luo; Fenghuan Wei (Chemical Engineering Journal, 2024)

Efficient and environmentally friendly uric acid voltametric sensor based on Ni-MOF and carboxylated multi-walled carbon nanotubes nanocomposites - Aiting Chen; Nana Tang; Yanping Wei; Shuting Shi; Chuanqin Zhou; Quanguo He; Jianhua Ding (Journal of Environmental Chemical Engineering, 2024)

Quinary metal oxide NiCoMnCeCaOx nanorod as a multifunctional catalyst towards hydrogen production from ethanol steam reforming: Synergistic effect of polymetallic component - Mingzheng Liao; Chunrun Qin; Liujie Xu; Sihan Guo; Chao Wang; Yi Li; Wei Liu; Qingbin Song; Ying Chen; Yanping Du (Chemical Engineering Journal, 2024)

Understandings in surface metal exsolution of NiFeZn ternary alloy/spinel in ethanol steam reforming: The key to hydrogen production - Mingzheng Liao; Wei Liu; Congkang Li; Sihan Guo; Yanyu Chen; Chao Wang; Ying Chen; Yanping Du (Chemical Engineering Journal, 2024)

Numerical simulation on staggered grids of three-dimensional brinkman-forchheimer flow and heat transfer in porous media - Wei Liu; Yingxue Song; Yanping Chen; Gexian Fan; Pengshan Wang; Kai Li (Computational Geosciences, 2024)

Design of Auto-Adaptive Drug Delivery System for Effective Delivery of Peptide Drugs to Overcoming Mucus and Epithelial Barriers - Ruihuan Ding; Yanping Li; Wei Zheng; Yiying Sun; Zhenyu Zhao; Houqian Zhang; Ranran Yuan; Aiping Wang; Kaoxiang Sun; Hongbo Wang; Yanan Shi (The AAPS Journal, 2024)

Evolutionary trajectory of TRPM2 channel activation by adenosine diphosphate ribose and calcium - Cheng Ma; Yanping Luo; Congyi Zhang; Cheng Cheng; Ning Hua; Xiaocao Liu; Jianan Wu; Luying Qin; Peilin Yu; Jianhong Luo; Fan Yang; Lin-Hua Jiang; et al. (Science Bulletin, 2024)

The effects of queen mandibular pheromone on Nosema (Vairimorpha) ceranae infections in caged honey bees - Wei-Fone Huang; Ama Safo-Mensa; Evan Palmer-Young; Jay D. Evans; Yanping Chen (Journal of Invertebrate Pathology, 2024)

Understanding the variability of ground-level ozone and fine particulate matter over the Tibetan plateau with data-driven approach - Haobin Zhong; Ling Zhen; Lin Yang; Chunshui Lin; Qiufang Yao; Yanping Xiao; Qi Xu; Jinsong Liu; Baihua Chen; Haiyan Ni; Wei Xu (Journal of Hazardous Materials, 2024)

N-acyl homoserine lactones (AHLs) enhanced removal of cadmium and other pollutants by algae-bacteria consortia - Qingnan Yu; Jiale Chen; Menglei Ye; Yanping Wei; Chunhua Zhang; Ying Ge (Journal of Environmental Management, 2024)

Resistance of an intertidal oyster(Saccostrea mordax)to marine heatwaves and the implication for reef building - Shuming Guo; Jun Li; Xiaogang Yang; Yanping Qin; Yuexin Zhao; Jinkuan Wei; Haitao Ma; Ziniu Yu; Liqiang Zhao; Yuehuan Zhang (Science of The Total Environment, 2024)

Estimating and partitioning evapotranspiration in a film mulched cropland with shallow groundwater by the improved dual source model - Xingwang Wang; Qiangli Wei; Weishu Wang; Shuai Wang; Zailin Huo; Yanping Qu; Juan Lyu; Huimin Lei (Journal of Hydrology, 2024)

On the use of EST-SSR to analysis the genetic diversity of segetale rye from China - Yonghe Che; Yanping Yang; Lai Wei; Yunjie Yang; Xiaolei Wen; Juan Guo; Xinming Yang; Xiuquan Li; Weihua Liu; Lihui Li (Cereal Research Communications, 2024)

New insights into functional divergence and adaptive evolution of uncultured bacteria in anammox community by complete genome-centric analysis - Yi-Cheng Wang; Yanping Mao; Hui-Min Fu; Jin Wang; Xun Weng; Zi-Hao Liu; Xiao-Wei Xu; Peng Yan; Fang Fang; Jin-Song Guo; Yu Shen; You-Peng Chen (Science of The Total Environment, 2024)

Influence of organic sulfur gas-phase sulfation on the NH3-SCR activity of CeO2 catalyst: The competitive adsorption and conversion of CS2 and COS at a low hydrolysis temperature - Zhibo Xiong; Zhenchang Sun; Jiaxing Liu; Yanping Du; Yafei Zhu; Fei Zhou; Jing Jin; Qiguo Yang; Wei Lu (Fuel, 2024)

QTL mapping for agronomic traits in Agropyron Gaertn. CP population at the flowering stage - Yonghe Che; Jing Yang; Yutong He; Nan Song; Yanping Yang; Lai Wei; Xinming Yang; Yannong Zhang; Jinpeng Zhang; Haiming Han; Xiuquan Li; Shenghui Zhou; et al. (Euphytica, 2024)

Understanding the variable metal concentrations in estuarine oysters Crassostrea hongkongensis: A biokinetic analysis - Shaomei Yang; Yanping Li; Fengyuan Chen; Shanshan Chen; Xin Luo; Wei Duan; Yongyan Liao; Hao Jiang; Ke Pan (Marine Environmental Research, 2024)

Understanding the spatial and seasonal variation of the ground-level ozone in Southeast China with an interpretable machine learning and multi-source remote sensing - Haobin Zhong; Ling Zhen; Qiufang Yao; Yanping Xiao; Jinsong Liu; Baihua Chen; Wei Xu (Science of The Total Environment, 2024)

Structures and ion transport mechanisms of plant high-affinity potassium transporters - Jiangqin Wang; Yanping Luo; Fan Ye; Zhong Jie Ding; Shao Jian Zheng; Shuai Qiao; Yong Wang; Jiangtao Guo; Wei Yang; Nannan Su (Molecular Plant, 2024)

Intervention effects of fructooligosaccharide and astragalus polysaccharide, as typical antibiotic alternatives, on antibiotic resistance genes in feces of layer breeding: advantages and defects - Yanping Hu; Jingjing Wei; Yongze Yuan; Hongkui Wei; Yuanfei Zhou; Naidong Xiao; Juan Xiong; Zhuqing Ren; Jian Peng; Changzheng Cui; Zhongxin Zhou (Journal of Hazardous Materials, 2024)

Dual-Coordinated atomically dispersed Pt nanozymes evoke efficient pyroptosis for cancer immunotherapy - Jingqi Chen; Yanping Tang; Yan Lin; Xiuxin Lu; Lineng Wei; Shiyu Xia; Wenxin Niu; Weizhong Tang; Weiqing Zhang (Chemical Engineering Journal, 2024)

Characterization of the Ovarian Development and Associated Factors during the Breeding Migration of Coilia nasus in the Yangtze River - Shuwei Wei; Zhong Hua; Yanping Yang; Fengjiao Ma; Wei Han; Wei Zhang; Congping Ying; Yanmin Deng; Kai Liu (Fishes, 2024)
Coilia nasus is a typical anadromous migratory fish found in the lower reaches of the Yangtze River. Every year, C. nasus clusters offshore and swims upstream along the Yangtze River into the tributaries and lakes in the middle and lower reaches of the Yangtze River to breed. In this study, female C. nasus were collected as study subjects from the Chongming section of Shanghai, the Taizhou section of Jiangsu, and the Anqing section of Anhui. Their ovaries were used to examine tissue sections and investigate gene expression, including the follicle-stimulating hormone receptor (fshr), the luteinizing hormone receptor (lhr), kisspeptin-1 (kiss1), and forkhead box l2 (foxl2), which are related to reproductive development, while the serum levels of estrogen (including estradiol, E2) and progestins (including 17α,20β-dihydroxy-4-pregenen-3-one, 17α,20β-DHP) were also analyzed. Our results showed that, first, the growth period of the oocytes was small in stage II of ovarian development, in which both E2 and 17α,20β-DHP levels and gene expression were low. Then, in stage III, the growth period of the oocytes became large, and the yolk granules and oil droplets began to appear. Simultaneously, E2 and the expression of kiss1 and foxl2 were significantly elevated. Finally, stage IV was the period of a large amount of accumulation of nutrients in the oocytes, and 17α,20β-DHP levels and the expression of fshr and lhr were significantly elevated. These results enrich the theoretical study of ovarian development in the natural population of C. nasus, supplementing the biological basis of C. nasus reproduction and scientifically supporting the study of C. nasus population ecology and resource conservation.

Effects of saline water with different concentrations of calcium and magnesium ions on emitter clogging in drip irrigation integrated water–fertilizer system - Long Zhou; Chenchen Wei; Peiling Yang; Yunkai Li; Lili Zhangzhong; Yanping Su; Xin Wang; Xin He (Irrigation and Drainage, 2024)
The application of saline water in drip irrigation is severely constrained due to its high salt content, which causes precipitation and emitter clogging. Therefore, the effects of calcium and magnesium ions at 100, 150 and 200 mg/L in saline water coupled with humic acid nitrogen fertilizer on emitter clogging were studied. Compared with ground saline water, all treatments significantly increased the emitter clogging risk. In the calcium and magnesium ion treatment groups, clogging fouling increased by 23.94–58.35 and 14.55–51.21 mg/cm 2 , the discharge variation ratio (Dra) decreased by 22%–59% and 14%–49%, and the Christiansen coefficient of uniformity (CU) decreased by 29%–79% and 15%–74%, respectively. Higher ion concentrations caused more clogging. Saline water with a high calcium content caused more clogging. Under similar concentration conditions, the Dra and CU in high magnesium saline water were 9%–32% and 8%–51% higher, respectively. In addition, the increase in magnesium ion concentration changed the crystal form of carbonate, slowed the formation rate of precipitated dirt and significantly reduced the carbonate content by 19%–40%. Our results provide support for the popularization of saline water drip irrigation systems.

Fully space-confined donor-acceptor interaction for highly efficient thermally activated delayed fluorescence emitters - Wen-Cheng Chen; Ming-Hui Zheng; Yu-Lan Wu; Ru-Jia Wang; Jia-Ming Jin; Si-Wei Chen; Bo Liu; Jia-Xiong Chen; Yanping Huo; Shaomin Ji (Chemical Engineering Journal, 2024)

Tungsten and oxygen dual vacancies regulation of the S-scheme ZnSe/ZnWO4 heterojunction with local polarization electric field for efficient CO2 photocatalytic reduction - Ting Liang; Zebin Yu; Yuejing Bin; Shiming Zhang; Jingwen Wei; Yujia Liu; Tingting Zhu; Songyu Fan; Yuxiang Shen; Shuangfei Wang; Yanping Hou (Chemical Engineering Journal, 2024)

Engineering redirected NF-κB/OIP5 expression programs to enhance tumor responses to chemotherapy in bladder cancer - Binbin Zheng; Liman Niu; Haibo Xu; Yubin Yang; Yanping Chen; Chenguang Wang; Wei Chen; Weiren Huang (Science Bulletin, 2023)

Promotional effect of H2O introduction on the NH3-SCR activity of the gas-phase sulfated CeO2 catalyst by organic CS2+COS: Influence of H2O concentration - Jiaxing Liu; Yafei Zhu; Zhenchang Sun; Yanping Du; Zhibo Xiong; Fei Zhou; Jing Jin; Qiguo Yang; Wei Lu (Journal of Environmental Chemical Engineering, 2023)

Novel aloe emodin–hydroxyethyl piperazine hybrid dihydrochloride induces oral cancer CAL-27 cells apoptosis through ROS production, DNA damage and mitochondrial pathways - Xing Long; Peilin Yang; Lin Chen; Wen Zhong; Shaofeng Chen; Yanping Li; Shijie Lin; Wei Tian (Medicinal Chemistry Research, 2023)

Controlled synthesis of CuS with different morphology and pollution control of Hg0 in non-ferrous smelting flue gas - Jin Zhao; Xueqian Wu; Yanping Ma; Wei Liu; Zhen Li; Songjian Zhao (Fuel, 2023)

Nanopore Structure and Multifractal Characteristics of Continental Shale Oil Reservoir: A Case Study from Ziliujing Shales in the Sichuan Basin - Youzhi Wang; Wei Li; Xiandong Wang; Zhiguo Wang; Weiqi Ma; Yanping Zhu; Mengdi Sun; Bo Liu; Lijuan Cheng; Xiaofei Fu (Journal of Marine Science and Engineering, 2023)
Thermal maturity of the shales from the Ziliujing Formation of the Jurassic age in the Sichuan Basin is in the hydrocarbon generation window, which makes it a candidate for shale oil and gas development. The meso- and macropore characteristics and heterogeneity of shales are important factors affecting the occurrence and development of oil and gas. However, the meso- and macropores of the Ziliujing shales have not been systematically studied. Thus, the mineral compositions and total organic carbon (TOC) of samples from this formation, as well as its pore structure, are analyzed by low-temperature N2 adsorption technique. Moreover, the heterogeneity of the pores was determined by multifractal analysis. The results show that the Ziliujing shales can be classified into three types according to the distributions of mineral compositions of carbonate and mixed and argillaceous shales. Results revealed that the smallest meso- and macropore volume (PV), the smallest specific surface area (SSA), and the largest average pore diameter (APD) occur in the carbonate shales. However, the largest PV and SSA and the smallest APD are observed in the argillaceous shales. The porosity of carbonate shales is mainly concentrated between 5 nm and 30 nm. Compared with carbonate shales, the porosity with pore sizes less than 30 nm of mixed and argillaceous shales shows a rapid increase. Furthermore, inorganic minerals are the main factors affecting the pore distributions, while TOC shows a weak effect. Herein, clay minerals significantly increase the mesopore volume and the pore number with a size of less than 30 nm. The Dq-q curves reveal that the meso- and macropore distributions of Ziliujing shales show multifractal behavior, but the multifractal characteristics of pores of various shales are distinctly different. The information dimension D1, the Hurst exponent H, and the width of the right side D0–D10 are key indicators to distinguish the local variations within the pore structure of different types of shales. The carbonate shales have the largest multifractal spectra width and the smallest D1 and H, while the opposite trend is found for the argillaceous shales. Clay minerals reduce the heterogeneity of the meso- and macropore distributions and increase the pore connectivity. Nevertheless, the carbonate minerals exhibit a reverse trend. Finally, it was found that TOC does not impact pore complexity as much. Collectively, this study supports our understanding of the occurrence of shale oil within various reservoir facies, thereby providing a guideline for future explorations in the Ziliujing Formation of the Jurassic age in the Sichuan Basin.

Coupling isotopic signatures and partial extraction method to examine lead pollution in mangrove sediments - Zhenghua Tao; Jian Hu; Qingjun Guo; Rongfei Wei; Linlin Jiao; Yanping Li; Fengyuan Chen; Bailing Fan; Wenlu Lan; Ke Pan (Journal of Hazardous Materials, 2023)

Causal relationships between chronotype and risk of multiple cancers by using longitudinal data and Mendelian randomization analysis - Shanshan Tian; Longtao Huangfu; Sizhi Ai; Junwei Zheng; Le Shi; Wei Yan; Ximei Zhu; Qianwen Wang; Jiahui Deng; Yanping Bao; Suhua Chang; Lin Lu (Science China Life Sciences, 2023)

Isotopic signatures unveil the lead sources and migration in surface mangrove sediments - Zhenghua Tao; Guogan Peng; Fengyuan Chen; Qingjun Guo; Rongfei Wei; Jingli Liu; Yanping Li; Hao Jiang; Yongyan Liao; Ke Pan (Science of The Total Environment, 2023)

The component of the Chamaecyparis obtusa essential oil and insecticidal activity against Tribolium castaneum (Herbst) - Lirui Zhang; Yu Zhang; Yanping He; Huang Dai; Zaixi Shu; Wei Zhang; Jie Bi (Pesticide Biochemistry and Physiology, 2023)

Corn-straw-derived, pyridine-nitrogen-rich NCQDs modified Cu0.05Zn2.95In2S6 promoted directional electrons transfer and boosted adsorption and activation of CO2 for efficient photocatalytic reduction of CO2 to CO - Jinhang Yang; Yanping Hou; Jiangli Sun; Jingwen Wei; Shiming Zhang; Jiaxiang Liang; Zebin Yu; Hongxiang Zhu; Shuangfei Wang (Chemical Engineering Journal, 2023)

Nitrogen addition regulates the growth of Pinus tabuliformis by changing distribution patterns of endogenous hormones in different organs - Yuhang Peng; Keli Chen; Guoliang Wang; Jiawei Tan; Furong Wei; Yanping Ma (New Forests, 2023)

Detection of depression marker ASS1 in urine by gold nanoparticles based dual epitope-peptides imprinted sensor - Hong Wei; Zixia Wang; Yanping Wang; Jing Ma; Yan Chen; Min Guo; Yuanyuan Li; Yongling Du; Fangdi Hu (Analytica Chimica Acta, 2023)

Associations between residential greenness and asthma and allergic rhinitis in children: A systematic review and meta-analysis - Wei Liu; Kailun Liu; Jiao Cai; Shuang Ma; Minghan Yang; Quan Yang; Yanping Yuan (Sustainable Cities and Society, 2023)

Electron-buffer-mediated dual Z-scheme ZnSe/Ag2Se/AgBr heterojunction for efficient CO2 photocatalytic reduction - Ting Liang; Jingwen Wei; Shiming Zhang; Jinhang Yang; Jiangli Sun; Zuji Li; Zhihong Li; Zebin Yu; Shuangfei Wang; Yanping Hou (Journal of Environmental Chemical Engineering, 2023)

Molecular cloning, functional characterization and expression of the β-amyrin synthase gene involved in saikosaponin biosynthesis in Bupleurum chinense DC. - Yanping Mao; Hua Chen; Jun Zhao; Yuchan Li; Liang Feng; Yuping Yang; Yiguan Zhang; Ping Wei; Dabin Hou (Journal of Plant Biochemistry and Biotechnology, 2023)

Calycosin-7-glucoside promotes mitochondria-mediated apoptosis in hepatocellular carcinoma by targeting thioredoxin 1 to regulate oxidative stress - Xiaodong Wei; Yanping Zeng; Fancheng Meng; Tingpu Wang; Hebin Wang; Yijun Yuan; Dongmei Li; Yue Zhao (Chemico-Biological Interactions, 2023)

Computer-aided engineering of CRISPR-Cas proteins for enhanced human genome editing - Yangcan Chen; Yanping Hu; Shengqiu Luo; Xinge Wang; Bangwei Mao; Yi Chen; Jing Xu; Zhikun Li; Qi Zhou; Wei Li (Science China Life Sciences, 2023)

Ca2+-dependent TaCCD1 cooperates with TaSAUR215 to enhance plasma membrane H+-ATPase activity and alkali stress tolerance by inhibiting PP2C-mediated dephosphorylation of TaHA2 in wheat - Minghan Cui; Yanping Li; Jianhang Li; Fengxiang Yin; Xiangyu Chen; Lumin Qin; Lin Wei; Guangmin Xia; Shuwei Liu (Molecular Plant, 2023)

Removal of chlorine, microparticles and water from high-viscosity liquids by a sand filter coupling hydrocyclone - Aosong Wei; Jianping Li; Minjie Shan; Wenjie Lv; Jianqi Chen; Pengbo Fu; Yanping Liu; Weichun Xu; Li Dai; Hualin Wang (Process Safety and Environmental Protection, 2023)

Effects of solid-state fermentation with Bacillus subtilis Y4 on the quality of Yibin Yacai - Yuke Zou; Yixin Zhong; Qian Zhou; Zhenchao Jia; Qian Chen; Wei Xu; Yanping Wu; Shugu Wei; Kai Zhong; Hong Gao (Food Bioscience, 2023)

Preparation of recyclable and deformable POM microfiber for oil–water separation with nature-inspired top–bottom strategy - Wenbin Jin; Jingjing Wang; Hai Wan; Yuan Liang; Shuohan Huang; Yuwei Chen; Peng Wei; Qun Shao; Yanping Wang; Yong He; Yumin Xia (Chemical Engineering Journal, 2023)

Photocatalytic and oxidation mechanisms of Fe–Ag@AgCl: Effect on co-existing arsenic (III) and Escherichia coli - Yanping Cui; Qian Ye; Haili Wang; Xuewen Duo; Liang Peng; Wei Dong; Xiaoxiao Cui; Yue Lu; Yajie Li (Environmental Research, 2023)

S-scheme MIL-101(Fe) octahedrons modified Bi2WO6 microspheres for photocatalytic decontamination of Cr(VI) and tetracycline hydrochloride: Synergistic insights, reaction pathways, and toxicity analysis - Shijie Li; Chunchun Wang; Yanping Liu; Yazi Liu; Mingjie Cai; Wei Zhao; Xiaoguang Duan (Chemical Engineering Journal, 2023)

In situ transformation of bismuth-containing precursors into ultrathin bismuth nanosheets for enhanced electrochemical CO2 reduction - Aihao Xu; Dong Wei; Xiangyu Chen; Taishun Yang; Yanping Huang; Huibing He; Jing Xu (Chemical Engineering Journal, 2023)

Citric Acid and Poly-glutamic Acid Promote the Phytoextraction of Cadmium and Lead in Solanum nigrum L. Grown in Compound Cd–Pb Contaminated Soils - Yu Wang; Weidong Duan; Chao Lv; Zhuangzhuang Wei; Yanping Zhu; Qi Yang; Ying Liu; Zhenguo Shen; Yan Xia; Kun Duan; Lingtong Quan (Bulletin of Environmental Contamination and Toxicology, 2023)

The roles of bacteria in resource recovery, wastewater treatment and carbon fixation by microalgae-bacteria consortia: A critical review - Qingnan Yu; Xinyu Pei; Yanping Wei; Sadiq Naveed; Siting Wang; Mengxuan Chang; Chunhua Zhang; Ying Ge (Algal Research, 2023)

Carbonate dynamics in a tropical coastal system in the South China Sea featuring upwelling, river plumes and submarine groundwater discharge - Wei Yang; Xianghui Guo; Zhimian Cao; Jianzhong Su; Liguo Guo; Lifang Wang; Yi Xu; Tao Huang; Yan Li; Yanping Xu; Zhe Wang; Guizhi Wang; et al. (Science China Earth Sciences, 2022)

Study on the Individual Coloring Mechanism of Iridescent Cells in the Mantle of the Boring Giant Clam, Tridacna crocea - Yunqing Li; Yinyin Zhou; Jinkuan Wei; Gongpengyang Shi; Qingliang Liao; Shuming Guo; Zihua Zhou; Jun Li; Yanping Qin; Haitao Ma; Ziniu Yu; Yuehuan Zhang (Frontiers in Marine Science, 2022)
Giant clams are marine bivalves that inhabit Indo-Pacific coral reefs. The boring giant clam, Tridacna crocea , exhibits bright and conspicuous mantle coloration based on the specialized cells (iridocytes) that generate structural colors. In order to illustrate the coloring mechanism of individual iridocytes, the reflection spectra curve of iridocytes was obtained by a micro-hyperspectral imager. TEM images were obtained to show the inner nanostructures of iridocytes. FDTD simulation was conducted to analyze the relationship between the color of iridocytes and the unique lamellar structure. We found that the laminae in the regular arrangement within cells govern the coloration of individual iridocytes. With the gradual increase of lamellar thickness and spacing, the color of the structure varies from bright violet to orange-red, forming a full visible spectrum. This study provides a new understanding of the various colors produced by individual iridocytes.

Correction to: Spindle‑related brain activation in patients with insomnia disorder: An EEG‑fMRI study - Yan Shao; Guangyuan Zou; Serik Tabarak; Jie Chen; Xuejiao Gao; Ping Yao; Jiayi Liu; Yuezhen Li; Nana Xiong; Wen Pan; Mengying Ma; Shuqin Zhou; et al. (Brain Imaging and Behavior, 2022)

Spindle-related brain activation in patients with insomnia disorder: An EEG-fMRI study - Yan Shao; Guangyuan Zou; Serik Tabarak; Jie Chen; Xuejiao Gao; Ping Yao; Jiayi Liu; Yuezhen Li; Nana Xiong; Wen Pan; Mengying Ma; Shuqin Zhou; et al. (Brain Imaging and Behavior, 2022)

Molecular epidemiology and clinical characterization of human rhinoviruses circulating in Shanghai, 2012-2020 - Haixia Jiang; Tianyun Yang; Chunyi Yang; Yanping Lu; Zhigang Yi; Qin Zhang; Wei Wang (Archives of Virology, 2022)

Localization and regulatory function of Yin Yang 1 (YY1) in chicken testis - Ligen Chen; Lingyun Qiao; Yan Guo; Ying Huang; Wei Luo; Yanping Feng (Molecular Genetics and Genomics, 2022)

Simvastatin Blocks Reinstatement of Cocaine-induced Conditioned Place Preference in Male Mice with Brain Lipidome Remodeling - Wei Xu; Yuman He; Jiamei Zhang; Hongchun Li; Xuemei Wan; Menglu Li; Yonghai Wang; Rui Xu; Haoluo Zhang; Yanping Dai; Haxiaoyu Liu; Linhong Jiang; et al. (Neuroscience Bulletin, 2021)

Circulating microRNA-30a-5p, microRNA-101-3p, microRNA-140-3p and microRNA-141-3p as potential biomarkers for dexmedetomidine response in pediatric patients - Xinmei Cai; Bilian Li; Wei Wei; Yanping Guan; Xue Bai; Min Huang; Yaying Huang; Lili Rong; Xingrong Song; Guoping Zhong (European Journal of Clinical Pharmacology, 2021)

Insight into the Interaction Between Microplastics and Microorganisms Based on a Bibliometric and Visualized Analysis - Yanping Jiang; Wanjun Xia; Rui Zhao; Mengge Wang; Jinfeng Tang; Yongjun Wei (Bulletin of Environmental Contamination and Toxicology, 2021)

Molecular Cloning and Characterization of FAD6 Gene from Chia (Salvia hispanica L.) - Yufei Xue; Lejing Li; Xuemei Liu; Huanhuan Jiang; Yanping Zhao; Songzhen Wei; Na Lin; Yourong Chai (Biochemical Genetics, 2021)

SETD4 in the Proliferation, Migration, Angiogenesis, Myogenic Differentiation and Genomic Methylation of Bone Marrow Mesenchymal Stem Cells - Xiaomin Liao; Caixia Wu; Zhongming Shao; Shuya Zhang; Yuan Zou; Keke Wang; Yanping Ha; Jingci Xing; Axiu Zheng; Zhihua Shen; Shaojiang Zheng; Junli Guo; et al. (Stem Cell Reviews and Reports, 2021)

Genetic Recombination of the Mantle Color Pattern of Two Boring Giant Clam (Tridacna crocea) Strains - Junjie Wang; Zihua Zhou; Haitao Ma; Jun Li; Yanping Qin; Jinkuan Wei; Xingyou Li; Qingliang Liao; Yunqing Li; Gongpengyang Shi; Yinyin Zhou; Yuehuan Zhang; et al. (Frontiers in Marine Science, 2021)
According to the RGB law display, the polymorphism of the giant clam mantle color pattern is through four iridocytes. The boring giant clam ( Tridacna crocea ) exhibits diverse mantle colors, including blue, green, purple, gold, and orange. In order to evaluate the genetic laws driving these mantle color patterns, a complete diallel cross between two color strains [blue strain (only blue iridocyte) and the yellow-green strain (yellow and green iridocytes)] was performed. Using a single-to-single mating system, two intra-strain crosses (BB and YY) and two reciprocal inter-strain crosses (BY and YB) were produced in triplicates. Higher fertilization rate and hatching rate were observed in all experimental groups, suggesting that there was no sperm–egg recognition barrier between the two strains. In the grow-out stage, the size of the reciprocal hybrids was larger than that of the two pure strains with a degree of heterosis. In addition, compared with the two pure strains, the hybrids have higher larval metamorphosis rate and higher survival rate. At 1 year of age, the mantle color pattern of pure strains showed 100% stable inheritance, while the reciprocal hybrids exhibited colorful patterns (a combination of blue, yellow, and green), suggesting that there was a genetic recombination of the mantle colors during the stable expression period. These results provide a theoretical basis for the formation of the mantle color of giant clam and its genetic segregation law, as well as provide guidance for genetic breeding of giant clams.

LncRNA TRHDE-AS1 inhibit the scar fibroblasts proliferation via miR-181a-5p/PTEN axis - Yanping Wei; Tingting Wang; Ningning Zhang; Yunyun Ma; Siji Shi; Ruxing Zhang; Xianzhao Zheng; Lindong Zhao (Journal of Molecular Histology, 2021)
Hypertrophic scar (HS), a fibroproliferative disorder caused by abnormal wound healing after skin injury, which is characterized by excessive deposition of extracellular matrix and invasive growth of fibroblasts. Recent studies have shown that some non-coding RNA implicated the formation of HS, but the mechanism remains unclear. In this study, we found that lncRNA TRHDE-AS1 was downregulated in HS tissues and HSFs, and the level of lncRNA TRHDE-AS1 negatively correlated with the level of miR-181a-5p in HS tissue and HSFs. Overexpressed lncRNA TRHDE-AS1 significantly suppressed miR-181a-5p level, while promoted HSFs apoptosis and inhibited HSFs proliferation. Further study shown that PTEN was a direct target of miR-181a-5p, and lncRNA TRHDE-AS1 served as a molecular sponge for miR-181a-5p to regulate the expression of PTEN. Overexpression of PTEN could eliminate lncRNA TRHDE-AS1-mediated proliferation suppression of HSFs. In conclusion, our study suggested that lncRNA TRHDE-AS1/miR-181a-5p/PTEN axis plays an important role in promoting hypertrophic scar formation, which may be effectively used as a therapeutic target for hypertrophic scar treatment.

Effects of Symbiodiniaceae Phylotypes in Clades A–E on Progeny Performance of Two Giant Clams (Tridacna squamosa and T. crocea) During Early History Life Stages in the South China Sea - Chao Long; Yuehuan Zhang; Yunqing Li; Jun Li; Zihua Zhou; Yanping Qin; Xingyou Li; Haitao Ma; Jinkuan Wei; Yinyin Zhou; Zohaib Noor; Lijuan Long; et al. (Frontiers in Marine Science, 2021)
Unlike most bivalves, giant clams (tridacnids) harbor symbiotic microalgae (zooxanthellae) in their other fleshy bodies. The effects of mixed populations of zooxanthellae on larval metamorphosis has been reported in several papers, but there have been very few studies on the effects of single zooxanthella species on the establishment of symbiosis in giant clams. In this study, we obtained five pure zooxanthella species (clades A3, B1, C1, D1, E1) from antler coral by molecular identification, and analyzed their effects on the larval metamorphosis and progeny performance of two giant clams, Tridacna squamosa and T. crocea , in the South China Sea. Clam larvae with all five zooxanthella species underwent larval settlement and metamorphosis, and formed the zooxanthellal tubular system. There was some variation in metamorphic rate and time to metamorphosis between clams with different zooxanthella species, but no significant differences in size at metamorphosis. After metamorphosis, larvae with all zooxanthella types continued to develop normally. Mantle color was consistent within clam species and zooxanthella species had no effect on mantle color. However, clam progeny with clade E1 zooxanthellae were smaller than progeny with the other four zooxanthella clades (A3, B1, C1, and D1). Survival rate was over 90% for all progeny and there were no significant differences in survival between progeny with Symbiodinium clades A–E during the entire culture process. Two-way ANOVA analysis revealed that giant clam species was the main factor influencing progeny growth, with some variation in growth attributable to zooxanthella type. Our results provide new information on both the symbiotic relationship between giant clams and zooxanthellae and the mantle coloration of giant clams, and will be useful in giant clam seed production and aquaculture.

Acetylation of BmAtg8 inhibits starvation-induced autophagy initiation - Shengjie Xue; Fuxiang Mao; Dongbing Hu; Huihui Yan; Jihai Lei; Enoch Obeng; Yuefan Zhou; Yanping Quan; Wei Yu (Molecular and Cellular Biochemistry, 2019)

Identification and molecular characterization of Serratia marcescens phages vB_SmaA_2050H1 and vB_SmaM_2050HW - Changyu Tian; Jiangtao Zhao; Zheng Zhang; Xiao Chen; Xiao Wei; Huan Li; Weishi Lin; Yuehua Ke; Lingfei Hu; Aimin Jiang; Ruo Feng; Wenhui Yang; et al. (Archives of Virology, 2019)

Genetic diversity and pathogenicity dynamics of Magnaporthe oryzae in the Wuling Mountain area of China - Xin Xu; Wu Yang; Ke Tian; Jie Zheng; Xinqiong Liu; Kai Li; Wei Lu; Yanping Tan; Yonghua Qin; Chuntai Wang (European Journal of Plant Pathology, 2019)

The effects of air temperature and precipitation on the net primary productivity in China during the early 21st century - Qianfeng Wang; Jingyu Zeng; Song Leng; Bingxiong Fan; Jia Tang; Cong Jiang; Yi Huang; Qing Zhang; Yanping Qu; Wulin Wang; Wei Shui (Frontiers of Earth Science, 2018)

Probiotic Properties and Cellular Antioxidant Activity of Lactobacillus plantarum MA2 Isolated from Tibetan Kefir Grains - Wei Tang; Chao Li; Zengguo He; Fen Pan; Shuo Pan; Yanping Wang (Probiotics and Antimicrobial Proteins, 2018)

Dioxin-like polychlorinated biphenyls in marine fish from Shandong, China, and human dietary exposure - Yanping Cao; Dafeng Jiang; Fenghua Li; Jindong Chen; Wei Li; Yanni Jiao; Lu Li (Food Additives & Contaminants Part B-Surveillance, 2018)

Colonization and Gut Flora Modulation of Lactobacillus kefiranofaciens ZW3 in the Intestinal Tract of Mice - Zhuqing Xing; Wei Tang; Ying Yang; Weitao Geng; Rizwan Ur Rehman; Yanping Wang (Probiotics and Antimicrobial Proteins, 2018)

Position and Angular Misalignment Analysis for Implantable Wireless Power Transfer System Based on Magnetic Resonance - Fei-Xiang Gong; Zhiqiang Wei; Haokun Chi; Bo Yin; Ying Sun; Yanping Cong; Mingui Sun (Journal of Medical and Biological Engineering, 2017)

Changes in endogenous hormones and H2O2 burst during shoot organogenesis in TDZ-treated Saussurea involucrate explants - Bin Guo; Wei He; Yan Zhao; Yandi Wu; Yanping Fu; Juan Guo; Yahui Wei (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Functional and bioinformatics analysis of an exopolysaccharide-related gene (epsN) from Lactobacillus kefiranofaciens ZW3 - Jingrui Wang; Wei Tang; Yongna Zheng; Zhuqing Xing; Yanping Wang (Archives of Microbiology, 2016)

A Comprehensive Analysis of Carotenoid Cleavage Dioxygenases Genes in Solanum Lycopersicum - Yanping Wei; Hongjian Wan; Zhiming Wu; Rongqing Wang; Meiying Ruan; Qingjing Ye; Zhimiao Li; Guozhi Zhou; Zhuping Yao; Yuejian Yang (Plant Molecular Biology Reporter, 2016)

Pharmacodynamics and Pharmacokinetics of Levobupivacaine Used for Epidural Anesthesia in Patients with Liver Dysfunction - Juhong Ran; Yanping Wang; Fangkun Li; Wei Zhang; Minyu Ma (Cell Biochemistry and Biophysics, 2015)

Reproductive management through integration of PGD and MPS-based noninvasive prenatal screening/diagnosis for a family with GJB2-associated hearing impairment - WenPing Xiong; DaYong Wang; Yuan Gao; Ya Gao; HongYang Wang; Jing Guan; Lan Lan; JunHao Yan; Liang Zong; Yuan Yuan; Wei Dong; SeXin Huang; et al. (Science China Life Sciences, 2015)

Effects of active, passive, and combined smoking on cervical cancer mortality: a nationwide proportional mortality study in Chinese urban women - Jingmei Jiang; Haiyu Pang; Boqi Liu; Philip C. Nasca; Biao Zhang; Yanping Wu; Wei Han; Margaret Gates; Tao Lu; Xiaonong Zou; Fang Xue; Lei Hou; et al. (Cancer Causes & Control, 2015)

Genetic diversity and demographic history of the endangered and endemic fish (Platypharodon extremus): implications for stock enhancement in Qinghai Tibetan Plateau - Junhu Su; Weihong Ji; Yanping Zhang; Dianne M. Gleeson; Zhongyu Lou; Jing Ren; Yanming Wei (Environmental Biology of Fishes, 2015)

CRP Gene polymorphism contributes genetic susceptibility to dyslipidemia in Han Chinese population - Wenbin Wei; Song Yang; Yingru Qiu; Hairu Wang; Xianghai Zhao; Yanping Zhao; Yun Li; Ming Wu; Yanchun Chen; Wen Wang; Xiaoming Shi; Sijun Liu; et al. (Molecular Biology Reports, 2014)

Association study of common variations of FBN1 gene and essential hypertension in Han Chinese population - Jinfeng Chen; Song Yang; Xianghai Zhao; Jiahui Shen; Hairu Wang; Yanchun Chen; Yanni Ji; Wen Wang; Wei Zhou; Xuecai Wang; Junming Tang; Xiangfeng Lu; et al. (Molecular Biology Reports, 2014)

Growth and yield of oleic sunflower (Helianthus annuus L.) under drip irrigation in very strongly saline soils - Shuqin Wan; Yanping Jiao; Yaohu Kang; Shufang Jiang; Junli Tan; Wei Liu; Jing Meng (Irrigation Science, 2013)

Therapy with Astragalus polysaccharides rescues lipotoxic cardiomyopathy in MHC-PPARα mice - Wei Chen; Wenjie Chen; Yanping Xia; Xuelan Zhao; Hao Wang; Maohua Yu; Yiming Li; Hongying Ye; Yu Zhang (Molecular Biology Reports, 2013)

The nuclear translocation of endostatin is mediated by its receptor nucleolin in endothelial cells - Nan Song; Yanping Ding; Wei Zhuo; Ting He; Zhiguang Fu; Yang Chen; Xiaomin Song; Yan Fu; Yongzhang Luo (Angiogenesis, 2012)

Preliminary assessment of heavy metal contamination in surface water and sediments from Honghu Lake, East Central China - Ying Hu; Shihua Qi; Chenxi Wu; Yanping Ke; Jing Chen; Wei Chen; Xiangyi Gong (Frontiers of Earth Science, 2012)

RNA interference-mediated silencing of iASPP induces cell proliferation inhibition and G0/G1 cell cycle arrest in U251 human glioblastoma cells - Guilin Li; Renzhi Wang; Jun Gao; Kan Deng; Junji Wei; Yanping Wei (Molecular and Cellular Biochemistry, 2011)

Genetic variation in the GCKR gene is associated with non-alcoholic fatty liver disease in Chinese people - Zhen Yang; Jie Wen; Xiaoming Tao; Bin Lu; Yanping Du; Mei Wang; Xuanchun Wang; Weiwei Zhang; Wei Gong; Charlotte Ling; Songhua Wu; Renming Hu (Molecular Biology Reports, 2011)

Alteration of integrin-associated protein (CD47) on experimental porcine eperythrozoonosis - Wei Li; Ning Du; Binrui Xu; Weixing Dong; Zhe Qu; Yong Wang; Yanping Sui (Veterinary Research Communications, 2008)